Tanggap Pertumbuhan Aren (Arenga Pinnata (Wurmb) Merr.) Diinokulasi Dengan Fungi Mikoriza Arbuskula Terhadap Pengapuran Di Lahan Pasca Tambang Batubara - Maria Paulina; Irdika Mansur; Ahmad Junaedi (Jurnal Silvikultur Tropika, 2018)
Sugar palm is one of local plants spesies that may potential for reclamation program because can be planted under the stands of forest crops. Forest crops can be shade seedlings sugar palm from direct sunlight because the growth of sugar palm is relatively slow. Sugar palm can be useful even without cutting down the trees. Previously, sugar palm had been planted at PT Berau Coal and had produced fruit. The research was conducted at coal post-mining land of PT Bukit Asam, Tanjung Enim, South Sumatera. The research using combination of AMF and liming treatment is as follows, ie MaK0 (control), Mak1 (seedling with AMF without inoculation; liming 30 g plant-1), MiK0 (AMF indigenous seedling inoculation; without liming), MiK2 (AMF indigenous seedling inoculation, liming 60 g plant-1), MmK0 (AMF mycofer seedling inoculation; without liming), and MmK3 (AMF mycofer seedling inoculation, liming 120 g plant-1). The results showed that sugar palm could be grown in the coal post-mining land. The combination of AMF and liming treatment did not significant effect on observed variables of plant height, rachis length, diameter, leaves number, number of spore and root cholonization. Sugar palm seedlings that have been infected with AMF could be grown and provide a good growth response even without liming.Keywords : Arbuscular Mycorrhizal Fungi (AMF), marginal land, sugar palm